2010
DOI: 10.1001/archneurol.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of 10 Antiepileptic Drugs in Older Adults With Epilepsy

Abstract: Patients: Four hundred seventeen outpatients 55 years and older newly taking any of the 10 most commonly prescribed AEDs between 2000 and 2005.Main Outcome Measure: The percentage of patients who remained taking the AED for 12 or more months (12-month "retention"). We also measured efficacy (12month seizure freedom) and adverse effects leading to dose change. Retention and seizure-freedom rates were analyzed by pairwise comparisons using 2 for the overall group and patients with refractory and nonrefractory di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 19 publications
3
66
0
4
Order By: Relevance
“…A more recent study comparing LTG and LEV in a population aged ≥55 years, showed similar 12-month retention rates for the two drugs; however, the study was retrospective and uncontrolled. 33 One limitation inherent to the design of the current trial is the inclusion of the LTG arm for which the study was not powered. There were a number of reasons that led to this decision.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study comparing LTG and LEV in a population aged ≥55 years, showed similar 12-month retention rates for the two drugs; however, the study was retrospective and uncontrolled. 33 One limitation inherent to the design of the current trial is the inclusion of the LTG arm for which the study was not powered. There were a number of reasons that led to this decision.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that, without controlling for severity, lamotrigine had the highest 12-month retention rate (79%), which was significantly higher than carbamazepine (48%), gabapentin (59%), oxcarbazepine (24%), phenytoin (59%), and topiramate (56%). The retention rate for levetiracetam (73%) was the second highest and was significantly higher than those of carbamazepine and oxcarbazepine were (Arif et al, 2010). The EULEV cohort study evaluated the rates and factors associated with continuation of levetiracetam after 1 year.…”
Section: Retention Ratesmentioning
confidence: 99%
“…Secondly, we assessed the effects of age and gender on retention rates of all eight AEDs due the fact that currently there is a lack of specific prescribing guidance for these subgroups of people with epilepsy [9].…”
Section: Introductionmentioning
confidence: 99%